2014
DOI: 10.3126/jcmc.v4i2.10853
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat versus subcutaneous fat: comparison of their association with type 2 diabetes mellitus

Abstract: To compare abdominal visceral fat with subcutaneous fat in relation to their association with type 2 diabetes. Abdominal fat distribution was measured using Computed Tomography in 60 subjects (30 diabetics and 30 non-diabetics). Computed tomography images obtained at two intervertebral locations L2-L3 and L4-L5 were used to measure areas of total fat, visceral fat and subcutaneous fat using slice thickness of 5mm and attenuation range of -190 to -30 Hounsfield units. Data were analyzed using logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
2
0
0
Order By: Relevance
“…The BMI of the diabetic women was signifi cantly known as central or visceral obesity, was more closely related to T2DM than the general obesity, as visceral fat was more metabolically active and produced more insulin resistance. [6][7][8][9] Similar data we observed in Bulgarian women aged 40-60 with a diagnosis of T2DM. The values of the '% fat higher than that of the healthy controls (p<0.001) ( Table 3).…”
Section: Resultssupporting
confidence: 84%
“…The BMI of the diabetic women was signifi cantly known as central or visceral obesity, was more closely related to T2DM than the general obesity, as visceral fat was more metabolically active and produced more insulin resistance. [6][7][8][9] Similar data we observed in Bulgarian women aged 40-60 with a diagnosis of T2DM. The values of the '% fat higher than that of the healthy controls (p<0.001) ( Table 3).…”
Section: Resultssupporting
confidence: 84%
“…It has been found that abdominal obesity, also known as central or visceral obesity, was more closely related to T2DM than the general obesity. The visceral fat is more metabolically active and produces more insulin resistance [6,7,8,9]. Similar data were observed in Bulgarian men aged 60-80, with a diagnosis T2DM.…”
Section: Discussionsupporting
confidence: 78%